A new Group of liquid reactive nitrogen and nitrogen-phosphorus flame retardants for self-extinguishing polyurethane expanded polymers. Part II. Applications to flexible polyurethane foams - Pietruszka, N.; Brzozowski, Z.; Żabski, L. (Polimery, 2022)
A method is described to produce self-extinguishing flexible polyurethane foams (PTPUR) containing new liquid reactive nitrogen-phosphorus flame retardants based on melamine. Selected property data of the foams are given.